Correction to: First results on survival from a large Phase 3 clinical trial of an autologous dendritic cell vaccine in newly diagnosed glioblastoma - Linda M. Liau; Keyoumars Ashkan; David D. Tran; Jian L. Campian; John E. Trusheim; Charles S. Cobbs; Jason A. Heth; Michael Salacz; Sarah Taylor; Stacy D. D’Andre; Fabio M. Iwamoto; Edward J. Dropcho; et al. (Journal of Translational Medicine, 2018)
Following publication of the original article [1], the authors reported an error in the spelling of one of the author names. In this Correction the incorrect and correct author names are indicated and the author name has been updated in the original publication. The authors also reported an error in the Methods section of the original article. In this Correction the incorrect and correct versions of the affected sentence are indicated. The original article has not been updated with regards to the error in the Methods section.